THE USE OF “ELSA” APPLICATION TO IMPROVE STUDENTS SPEAKING SKILLS AT EIGTH GRADE STUDENTS AT SMP N 8 SATAP TONDANO. - Masekan, Safira; Liando, Nihta V. F.; Rorintulus, Olga A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This study sought to ascertain whether eighth grade students at SMP Negeri 8 SATAP Tondano could speak more fluently after using the ELSA application to learn English. Pre-experimental research using pre- and post-tests in a single class was the main focus of this study. The fifty students in class eight of the academic year 2022–2023 make up the population of this study. The researcher used a single class, class VIII, which had 19 students as the research sample. During the speaking ability test, data were collected for the pre- and post-test dialogues. The study’s findings suggest that using the ELSA application can help students’ speaking abilities, including their grammar, content, pronunciation, vocabulary, and fluency. This is demonstrated by the students’ average pre-test score of 58,26, which rises to 81.47 in the post-test. This indicates that students in class eight at SMP Negeri 8 SATAP Tondano can enhance their speaking abilities by using the ELSA application to learn English